2008
DOI: 10.1038/ng.262
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association data identifies four new susceptibility loci for colorectal cancer

Abstract: Genome-wide association (GWA) studies have identified multiple loci at which common variants modestly influence the risk of developing colorectal cancer (CRC). To enhance power to identify additional loci with similar effect sizes, we conducted a meta-analysis of two GWA studies, comprising 13,315 individuals genotyped for 38,710 common tagging SNPs. We undertook replication testing in up to eight independent case-control series comprising 27,418 subjects. We identified four previously unreported CRC risk loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
219
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(233 citation statements)
references
References 41 publications
12
219
2
Order By: Relevance
“…Large genome-wide association studies (GWAS) have been performed, and to date 7 GWAS in colorectal cancer have identified 10 risk loci associated with a risk of developing colorectal cancer [144,145,146,147,148,149,150]. These genetic markers may direct screening and preventive therapy approaches, but may also identify unappreciated disease biology.…”
Section: The Success Of and Future Hope For Personalized Therapymentioning
confidence: 99%
“…Large genome-wide association studies (GWAS) have been performed, and to date 7 GWAS in colorectal cancer have identified 10 risk loci associated with a risk of developing colorectal cancer [144,145,146,147,148,149,150]. These genetic markers may direct screening and preventive therapy approaches, but may also identify unappreciated disease biology.…”
Section: The Success Of and Future Hope For Personalized Therapymentioning
confidence: 99%
“…In colorectal cancer, 10 risk SNP loci were reported at chromosomal bands 8q24, 18q21 [25], 8q23.3, 10p14 [7], 11q23 [5] [6], 15q13.3 [7], 14q22.2, 16q22.1, 19q13.1 and 20p12.3 [5]. In these studies, large cohorts of colorectal cancer patients and cancer free individuals were screened for novel and confirmed loci and presentation of susceptibility loci should be a step toward blood based screening for colorectal cancer risk [5] [16] [17]. Odds ratios generated in the studies ranged from 1.1 -1.5, which was low even when several DNA loci were combined [16] [17] [26].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has appeared that CNVs are common and involve a great proportion of the human genome and may be involved in cancer development [2] [3] [9]- [15]. Such findings may be utilized to improve public health care activities [5] [11] [16] [17], where DNA CNVs may provide additional information in screening of phenotypes compared to SNPs [8] [18] [19]. Therefore, the aim of this study was to search for CNVs in colon mucosa, as related to colon cancer, in 60 patients at their primary operation for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was recently applied to multiple GWA studies of colorectal cancer, combining work done by 2 groups in the UK [70]. Another study used this for type 2 diabetes, combining 3 GWA studies in subjects of European descent [71].…”
Section: Developing Methods For Synthesis and Meta-analysis Of Genetimentioning
confidence: 99%